2018
DOI: 10.1016/j.ejphar.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive binding properties of the negative allosteric modulator, [ 3 H]SB269,652, at recombinant dopamine D 3 receptors

Abstract: Recently, employing radioligand displacement and functional coupling studies, we demonstrated that SB269,652 (N-[(1r,4r)-4-[2-(7-cyano-1,2,3,4-tetrahydroisoquinolin-2-yl)ethyl]cyclohexyl]-1H-indole-2-carboxamide) interacts in an atypical manner with dopamine D receptor displaying a unique profile reminiscent of a negative allosteric ligand. Here, we characterized the binding of radiolabelled [H]SB269,652 to human dopamine D receptor stably expressed in Chinese Hamster Ovary cells. Under saturating conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…24 AAPs are known to bind to various neurotransmitters. 25 However, the mechanisms underlying the metabolic side effects of AAPs are largely unknown, but speculation abounds. Several studies have advanced the view that the involvement of genes that encode histamine, α adrenergic and dopamine D 2 receptors are likely to be involved in metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…24 AAPs are known to bind to various neurotransmitters. 25 However, the mechanisms underlying the metabolic side effects of AAPs are largely unknown, but speculation abounds. Several studies have advanced the view that the involvement of genes that encode histamine, α adrenergic and dopamine D 2 receptors are likely to be involved in metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [21] synthesized and pharmacological characterization of novel trans-cyclopropylmethyl-linked bivalent ligands with dopamine D 3 receptor (D 3 R) allosteric interactions. Fasciani et al [55] suggested that SB269,652 behaves as a bitopic antagonist at unoccupied dopamine D 3 R, binding simultaneously to both orthosteric and allosteric sites, and as a pure negative allosteric modulator when receptors are occupied, and it can solely bind to an allosteric site. Notably, all bitopic ligands are allosteric, for example, MRS7395 and XAC488 are demonstrated to be competitive antagonists in nature.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Receptor selectivity—While orthosteric sites of GPCRs that bind the same or similar endogenous ligands are highly conserved due to evolutionary pressure, allosteric sites are less conserved, allowing for the accommodation of highly selective allosteric modulators. For instance, the negative allosteric modulator SB269652 is highly selective for D 3 receptor with 100–1000-fold less affinity for nearly all the other amine receptors [ 38 ].…”
Section: Allosteric Modulation Of Gpcrs and Influence On Receptor mentioning
confidence: 99%
“…SB269652 was originally synthesized by SmithKline Beecham in the effort to find new selective dopamine D 3 receptor antagonists [ 125 , 126 ]. Therefore, the radiolabeled [ 3 H]SB269652 shows a high binding affinity and selectivity for the dopamine D 3 receptor [ 38 ].…”
Section: Sb269652—a Prototypical Negative Allosteric Modulator Of mentioning
confidence: 99%
See 1 more Smart Citation